Un’urbanistica relazionale (Itinera, 2024)
The failure of contemporary Urbanism to cope with Climate Collapse has to do with its own approach to reality, which moves between imagination and the materialisation of human landscapes. As an answer to this weakness, two major Urbanism trends are, on the one hand, the exasperation of a hyper-technological and geo-engineering attitude and, on the other, the reframing of the nature and city relation. A paradigm shift that confronts climate emergency on a both planetary and territorial level.The traces of nature-city paradigm shift are at least three, recounted in the essay through some cases and research: the end of production and the emergence of a pluriversal “industrial nature”; the ecological turn and the urgency of “greening” strategies for cities; the failure of the traditional idea of “nature” and the need to reformulate the territorial project.What emerges is the possibility of a Relational Urbanism, in which the focus is mainly on the ways in which human and non-human actors interact, and not only on the ancestral debate on human rights and social control. Far from being a green utopia, the relational dimension of the project imposes itself as a collective intellectual risk and a necessary ethical commitment.
Keywords: Urbanism, Nature, Relationality, Landscape